The Protection of Overseas Interests of the “Belt and Road” Initiative: Taking Artificial Intelligence as the Perspective - Ren, Shuai (International Journal of Social Sciences and Public Administration, 2024)
"Belt and Road" initiative is an important part of China's overseas strategy, and the protection of overseas interests derived from it is fragile because of the lack of territorial jurisdiction protection. Take artificial intelligence as an example, the overseas interests of artificial intelligence derived from the “Belt and Road” initiative are mainly faced with the “long-arm jurisdiction” of Western countries led by the United States, and the disregard of international law by Western neorealism. Based on the field of artificial intelligence, this article puts forward suggestions on improving the overseas interests protection mechanism under the vision of the “Belt and Road” Initiative.